The Effectiveness of Audiovisual Media in Laboratory Learning on Improving Student Learning Outcomes during the Covid-19 Pandemic - Heryningsih, Wiwin Priyantari; Kuswanti, Ina; lubis, Dina putri utami (International Journal on ObGyn and Health Sciences, 2024)
Background: The COVID-19 pandemic has spread since the end of 2019 until now throughout the world. Educational institutions inevitably innovate face-to-face conventional learning into online distance learning. Online learning on cognitive achievement can be done, but a solution is needed for learning clinical skills both in the laboratory and in practice. This study aims to determine "The Effectiveness of Audiovisual Media in Laboratory Learning on Improving Student Learning Outcomes during the Covid-19 Pandemic". Research Methods: This type of quantitative research uses a quasi-experimental design method and uses a pretest–posttest one group design. The population involved were all active students of Stikes Yogyakarta Academic Year 2020/2021 totaling 164 people. The sampling technique used purposive random sampling. To find out the difference after and before treatment on the sample using Non Parametric analysis with the Wilcoxon Signed Rank Test technique. Results: There is an effect of audiovisual media in laboratory learning on improving student learning outcomes during the Covid-19 pandemic with Tcount -3.464> Ttabe1, 1.697 with a probability of 0.002. Conclusion: There is an effect of audiovisual media in laboratory learning on improving student learning outcomes during the Covid-19 pandemic